PENGARUH PELATIHAN "THE SECRET MEANING OF BROKER" TERHADAP KETERIKATAN KERJA PADA BROKER SAHAM - Yovita Karlina (CALYPTRA, 2014)
The purpose of this research is to know about correlation of work meaning as a calling and work engagement in Broker work life. How “the secret meaning of broker” training can improve the level of work engagement. This research discuss about Job Resources and Personal Resources as a factor to predict high or low level of work engagement. The method of this research is single case experimental pretest-posttest only. Participant (N=15) is the population of PT.X Securities. The method of data collection using questionnaire, observation and interview. The result of this research “the secret meaning of broker” training as a personal resources and job resources as a environmental, supervisory, organization system, social support togetherness increased work engagement